A new device for the removal of cochlear schwannoma: A temporal bone study - Sudhoff, Holger; Riemann, Conrad; Kim, Rayoung; Scholtz, Lars Uwe; Pfeiffer, Christoph J.; Goon, Peter; Todt, Ingo (Frontiers in Surgery, 2023)
Intra-labyrinthine schwannoma (ILS) is a rare mostly unilateral disease which causes deafness.Different intra-labyrinthine sites of ILS can occur and can be removed by different surgical approaches. Cochlear ILS are frequently partially hidden by the modiolus and therefore difficult to extirpate. Surgical techniques can be significantly traumatic, offer only limited surgical control of the removal and are time consuming. The aim of this present study was to demonstrate the performance and handling of a newly developed device for the removal of cochlear intra-labyrinthine schwannoma in temporal bone. Methods: In a temporal bone study with a prepared posterior tympanotomy, enlarged round window approach and an additional second turn access, a stiffened device with silicone rings was inserted and extracted gradually from the second turn access until the rings were visible in the second turn access. Results: Insertion and extraction out of the second cochlear access was easily performed. Pulling and pushing of the silicone rings through the modiolus & hidden parts of the basal turn was possible and worked like a pipe cleaner. Conclusion: This newly developed tissue removal device (TRD) in combination with the proposed surgical handling offer a new and less traumatic way to remove cochlear ILS.